Jezika v stiku: slovenščina in furlanščina. Prevzete besede in kalki - Skubic, Mitja (Slavistična revija, 2007)
The papaer investigates mutual linguistic influence between West Slovene dialects and Friulian alog the Soča river, where Slovene and Friulian, or more precisely, Western Slovene and the easternmost Friulian dialects are in direct cpntact, that is to say, thez have been sharing the same territory for over a thousand years. The article analyzes the words borrowed from the neighboring, contiguous language and semantic and syntactic calques, which in particular require close, long-term coexistence.
Keywords: calques; Eastern Friulian alog the Soča river; furlanščina; goriški govori; Goriško dialects; kalki; prevzete besede; Slovene language; slovenščina; Vzhodna obsoška furlanščina; Western Slovene dialects; zahodnoslovenski govori